The Role of Brand Image in Overall Purchasing Decisions Online at Marketplace - Gumilang, Risa Ratna; Ridwan, Zulkipli Marlinto (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
This research aims to analyze the role of brand image in online purchasing decisions in the marketplace. Brand images are believed to play an important role in influencing consumer purchasing behavior in the marketplace. This research uses a quantitative approach with a survey method involving 200 respondents who have made online purchases on the marketplace in the last 6 months. Data was collected through a questionnaire specifically designed to measure brand image perceptions and purchasing decisions. The results of the analysis show that brand image has a positive and significant relationship with online purchasing decisions. This finding underlines the importance of companies in building and maintaining a strong brand image to increase consumer purchasing decisions in the marketplace. This research also provides valuable insight for marketplace managers in developing features and services that can strengthen the brand image of sellers on their platforms